Fungsi Karunia Roh Kudus dalam Pelayanan Gereja Digital Berdasarkan 1 Korintus 12:1-11 - Astuti, Luh Suti; Bara, Marlinda Fitriani (Sekolah Tinggi Teologi Immanuel Sintang Kal-Bar, 2022)
This paper reviews the gift of the Holy Spirit in 1 Corinthians 12:1-11. The method used in writing this topic is a qualitative method with a descriptive approach. The role and function of the Holy Spirit based on 1 Corinthians 12: 1-11 is to enlighten believers in preaching the gospel. The purpose of the gift of the Holy Spirit is to help in the ministry of the Digital Church and to show that the power of God is more dominant than the powers of the universe. In preaching the gospel, the function of the gifts of the Holy Spirit has a very important role. Preaching the Gospel is the Great Commission of Jesus Christ, and the responsibility of believers. The purpose of this paper is to explain how the gifts of the spirit function in the ministry of the church in digital. In 1 Corinthians 12: 1-11 the Apostle Paul further explains how about healing in the church? In 1 Corinthians 12 there is an answer from Paul to the Corinthians' question about the gifts of the Spirit. There are various kinds of gifts: the gift of healing, the gift of prophecy, the gift of discernment of spirits, and the gift of tongues. These gifts are given for the purpose of assisting, helping and facilitating the ministry of preaching the gospel of the Kingdom of God.